Religious Moderation: A Model for Internalizing Inclusive Islamic Values in Student Education - Qurrotul Ainiyah; Dita Dzata Mirrota; Ma’rifatul Khasanah (Lembaga Penelitian, Penerbitan dan Pengabdian Masyarakat (LP3M) IAI Al Urwatul Wutsqo - Jombang, 2025)
This study aims to analyze the internalisation process of moderate Islamic values through mosque youth activities at SMAN 1 Jombang. Using a qualitative approach with the descriptive method, this study examines the concept of moderate Islamic values, the form of mosque youth activities in internalizing moderate Islamic values, and the process of instilling these values. Data collection was conducted through in-depth interviews, participatory observation, and documentation studies, with data analysis adapting the interactive model of Miles et al. The results showed that the concept of moderate Islamic values instilled at SMAN 1 Jombang includes tolerance, mutual respect, non-discrimination, and cooperation. The internalization of these values is done through various mosque youth activities such as yellow book studies, Qiraah, Al-Banjari, commemoration of Islamic holidays, and social activities. The internalization process is carried out through three stages, namely value transformation using the lecture method, value transaction using the question and answer method and exemplary, and transinternalisation through habituation and evaluation. This research contributes to the development of an internalisation model of moderate Islamic values in formal education institutions as a preventive effort against radicalism and extremism among the younger generation